Sustainable Tourism - Ways to Counteract the Negative Effects of Overtourism at Tourist Attractions and Destinations - Kruczek, Zygmunt (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint contains articles published as part of the Special Issue of "Sustainable Tourism: Ways to Counteract the Negative Effects of Overtourism at Tourist Attractions and Destinations" in the journal Sustainability in the "Tourism, Culture, and Heritage" section. It contains 13 articles presenting research on various aspects of overtourism: the attitudes of city dwellers towards overtourism, e.g., Krakow and Wrocław; the effects of tourism development in regions of natural value, e.g., the Tatra National Park; and areas adjacent to tourist routes. It looked at night-time tourism and the sharing economy, as well as how business models can be used to manage sustainable tourism. The phenomenon of overtourism in Tunisia, Brazil, and South Korea is described. The articles published in 2020 are very popular. They have been viewed by several thousand researchers and have been cited 300 times by other authors.